Mitochondrial Maturation in Human Pluripotent Stem Cell Derived Cardiomyocytes - Dao-Fu Dai; Maria Elena Danoviz; Brian Wiczer; Michael A. Laflamme; Rong Tian (Hindawi Limited, 2017)
Human pluripotent stem cells derived cardiomyocytes (PSC-CMs) have been widely used for disease modeling, drug safety screening, and preclinical cell therapy to regenerate myocardium. Most studies have utilized PSC-CM grown in vitro for a relatively short period after differentiation. These PSC-CMs demonstrated structural, electrophysiological, and mechanical features of primitive cardiomyocytes. A few studies have extended in vitro PSC-CM culture time and reported improved maturation of structural and electromechanical properties. The degree of mitochondrial maturation, however, remains unclear. This study characterized the development of mitochondria during prolonged in vitro culture. PSC-CM demonstrated an improved mitochondrial maturation with prolonged culture, in terms of increased mitochondrial relative abundance, enhanced membrane potential, and increased activity of several mitochondrial respiratory complexes. These are in parallel with the maturation of other cellular components. However, the maturation of mitochondria in PSC-CMs grown for extended in vitro culture exhibits suboptimal maturation when compared with the maturation of mitochondria observed in the human fetal heart during similar time interval.